2019 IEEE/CVF Conference on Computer Vision and Pattern Recognition (CVPR) 2019
DOI: 10.1109/cvpr.2019.00132
|View full text |Cite
|
Sign up to set email alerts
|

An Attention Enhanced Graph Convolutional LSTM Network for Skeleton-Based Action Recognition

Abstract: Skeleton-based action recognition is an important task that requires the adequate understanding of movement characteristics of a human action from the given skeleton sequence. Recent studies have shown that exploring spatial and temporal features of the skeleton sequence is vital for this task. Nevertheless, how to effectively extract discriminative spatial and temporal features is still a challenging problem. In this paper, we propose a novel Attention Enhanced Graph Convolutional LSTM Network (AGC-LSTM) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
427
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 786 publications
(461 citation statements)
references
References 36 publications
1
427
0
Order By: Relevance
“…To reason between different instances in visual question answering tasks, Xiong et al [47] proposed a graph matching module for investigating such relation. In sketch-based action recognition, several works showed that modeling interactions of sketch joint can achieve excellent performance [25], [26], [48]. Here, we show that explicitly exploiting the various and multi-scale temporal relations in videos can boost activity recognition accuracy.…”
Section: Related Workmentioning
confidence: 56%
“…To reason between different instances in visual question answering tasks, Xiong et al [47] proposed a graph matching module for investigating such relation. In sketch-based action recognition, several works showed that modeling interactions of sketch joint can achieve excellent performance [25], [26], [48]. Here, we show that explicitly exploiting the various and multi-scale temporal relations in videos can boost activity recognition accuracy.…”
Section: Related Workmentioning
confidence: 56%
“…Kalpit divided the skeleton graph into four subgraphs with joints shared across them and taught a recognition model using a part-based graph convolutional network [8]. AGC-LSTM [10] can not only capture features in spatial configuration and temporal dynamics but also explore the co-occurrence relationship between spatial and temporal domains.…”
Section: Skeleton-based Methodsmentioning
confidence: 99%
“…Therefore, graph-based neural networks have been used for action recognition instead of the traditional CNN networks because of the successful performance. Some graph-based neural networks [6][7][8][9][10] are dedicated to learning both spatial and temporal features for action recognition. Meanwhile, they focus on capturing the hidden relationships among vertices in space.…”
Section: Introductmentioning
confidence: 99%
“…Apart from the CNN-based approaches [20,77], Recurrent Neural Networks (RNNs) have also been popular [18,27,35,38,65,[67][68][69][70]. Since Long Short-term Memory (LSTM) [78] can model temporal dependencies as RNNs and even capture the co-occurrences of human joints, LSTM networks have also been a popular choice in human action recognition [31,33,36,37,73]. For instance, Zhu et al [69] presented an end-to-end deep LSTM network with a dropout step, Shahroudy et al [18] proposed a Part-aware Long Short-term Memory (P-LSTM) network to learn the long-term patterns of the 3D trajectories for each grouped body part, and Liu et al [36] introduced the use of trust gates in their spatio-temporal LSTM architecture.…”
Section: Related Workmentioning
confidence: 99%